Subsidized Diesel Fuel Distribution Post-Development Of The New Region Authority Strategy - abdul halim; Idqan Fahmi; Arief Safari (International Journal of Social Service and Research, 2023)
Papua has officially been divided into 4 regions, namely Papua,Central Papua, Highlands Papua, and South Papua effective June 2022.  The supply and distribution of subsidized fuel to each region has its own challenges, unpredicted weather, terrain, shallow rivers and the lack of infrastructure lead to very high operation cost. Apart from providing subsidized fuel, Pertamina has also to sell non-subsidized fuel in order to present in market competion among foreign companies that sell non-subsidized fuel in Indonesia. This research aims to evaluate, optimize and reformulate PT. Pertamina Patra Niaga strategy in managing supply and distribution of Subsidized Fuel to each region and business strategy in downsteam fuels market. The scope of this research is qualitative and quantitative descriptive and the data used are the combination of primary and secondary data. The primary data obtained through interviews and observations, and the secondary data obtained from PT. Pertamina Patra Niaga, BPH Migas, library research, journals and other literatures. The demand forecating, external environmental analysis (PESTEL), internal environmental analysis (Value Chain), industrial environmental analysis (SWOT), AHP and linear programming (LP) analysis were carried out in order to determine the alternative strategy. Based on the qualitative analysis, the result obtained that PT. Pertamina Patra Niaga has the strength of providing subsidized fuels, distribution network, sales outlets, facilities and infrastructure for distribution of subsidized fuels to all regions in Papua. PT. Pertamina Patra Niaga has high opportunity of success to win the market competition. To support the winning competition, the selected strategy that can be implemented is optimizing the subsidized diesel fuel distribution network and operational costs reduction strategy.